Hemodynamic and respiratory variation in the six-minute walk test in patients undergoing cardiac surgery: a cross-sectional study - Julia Casagrande; Emely Teixeira Bodnar; Eliane Roseli Winkelmann (Fisioterapia e Pesquisa)
ABSTRACT The six-minute walk test (6MWT) is commonly prescribed for cardiac surgery patients, yet the hemodynamic and respiratory variations during the test remain insufficiently described in this population. This study aimed to compare the hemodynamic and respiratory data, dyspnea sensation variation, and perceived exertion in the lower limbs during the 6MWT between the pre- and post-test periods. It also sought to analyze whether there is a difference in the variation between the pre and postoperative periods of elective cardiac surgery for the same variables. This cross-sectional study included 113 individuals undergoing elective cardiac surgery. The 6MWT was conducted the day before surgery and on the fourth postoperative day. Results showed a significant increase in hemodynamic variables, including HR, SBP, DBP (p ≤0.01) and dyspnea and lower limb exertion (p≤0.01), both pre and postoperatively; there was no variation in SpO2 both pre- (p=0.64) and postoperatively (p=0.45). The average distance covered decreased from 346.98±107.51 to 252.06±107.17 m after surgery. There was a greater variation in the mean difference between the pre- and post- test for HR before surgery (p=0.05) and a greater feeling of perceived exertion in the lower limbs after surgery (p=0.02). Between the pre and post-test, there was a physiological increase in hemodynamic data, sensation of perceived exertion, without SpO2 alteration, and functional decline in the distance covered between the pre- and postoperative periods of cardiac surgery. HR showed greater variation preoperatively, while exertion perceived in the lower limbs did so postoperatively, although this was clinically irrelevant.